Implications of plant functional traits and drought survival strategies for ecological restoration. Issue 2 (23rd August 2017) - Balachowski, Jennifer A.; Volaire, Florence A.
Abstract: Restoration of degraded grasslands through active revegetation often involves re‐establishing populations of native grasses, which must withstand increasing drought stress to persist beyond initial establishment. In perennial species, superior dehydration tolerance is expected to result in more conservative growth, but this trade‐off has seldom been studied among populations of herbaceous species. We measured seasonal growth and foliar and root functional traits under non‐limiting water conditions, followed by recovery after severe drought in four populations of Elymus glaucus, a perennial grass from California's Mediterranean‐climate region. We hypothesized that populations from harsher sites would be more dehydration tolerant, summer dormant and resource‐conservative. Dehydration tolerance and summer dormancy were associated with a more conservative strategy (lower productivity, lower specific leaf area and specific root length), as well as earlier reproductive phenology. Multivariate trait variation was associated with water availability in both the growing season and summer, while greater dehydration tolerance and summer dormancy were associated with increasing summer climatic water deficit. Synthesis and applications . Our study provides evidence of an intraspecific trade‐off between dehydration tolerance and rapid resource acquisition. We discuss the implication that restored populations with superior drought survival may therefore be less competitive, and recommend further investigation to inform plant materials selection protocols and management practices. Abstract : Our study provides evidence of an intraspecific trade‐off between dehydration tolerance and rapid resource acquisition. We discuss the implication that restored populations with superior drought survival may therefore be less competitive, and recommend further investigation to inform plant materials selection protocols and management practices.